The Land of the Dawning Sun: Italian gazes out to Albania from the beginning of 1900 to present day. - Calore, AnnaMaria (Academicus, 2019)
Over the first forty years of the last century the Italian View of Albania has changed in different ways, but always maintaining strong interest. Both the surprised and sometimes the astonished gaze of travelers and the one of those attracted by possible trade exchanges or the gaze on the soldiers convinced of having the task to Italianize Albania in 1939 "the land of dawning sun" separate frontally by a narrow stretch of the sea, symbolized hopes and promises. In the text of the country across the water that borders with itself the story the specific view (from francone wardon) to stand guard inevitably changed in to watch (from Sanskrit) that means to observe and know.